Pathological risk factors related to mother during pregnancy that lead to epilepsy in children - Mohammed, Halah; Al-Hakak, Asmaa (Journal of Biomedicine and Biochemistry, 2022)
Epilepsy is the most common neurological disorder related to abnormal electrical activity in the brain. The current study aims to identify the risk factors associated with epilepsy among children related to mothers. Methodology: A descriptive case-control study was adopted to achieve the stated objectives. An analytic case-control study, Non-Probability (a Purposive Sample) of (100) women of Children with epilepsy as the case group, and (100) women of healthy children without epilepsy as a control group. The reliability of the instrument is determined using Cronbach Alpha, and the Validity of questionnaires was determined through a panel of experts. The data are analyzed using descriptive and inferential statistics. Results: The study has shown that residency, mother exposure to domestic violence during pregnancy, mother exposure to an accident during pregnancy, and prolonged labor are significantly associated with epilepsy occurrence (the Odds ratio more than 1), so these factors are more likely to be risk factors associated with epilepsy occurrence. Conclusion: The study concludes that among the risk factors associated with epilepsy for the present study were residency, exposure to domestic violence, exposure to the accident (car accident, trauma, fall), and prolonged labor.